Prenatal Stress Reduces Learning and Memory in Pre-pubertal, Young, and Adult Rats of Both Sexes - Guerrero Aguilera María de los Angeles; Rubio Osornio María del Carmen; Galván Arzate Sonia; Retana-Márquez Socorro (Global Journal of Zoology - Peertechz Publications, 2017)
Prenatal stress (PS) induced by immobilization produces defi ciencies in spatial learning and information retrieval. These defi ciencies seem to be larger in males than in females, and have been explained as an effect of fetal exposure to high concentrations of maternal corticosterone during stress response. However, the effects of PS have only been assessed at a single time point and/or sex. In this work, the effect of PS on spatial learning and memory induced by immersion in cold water was evaluated in young and adult rats of both sexes. PS was induced during gestational days 15 through 21. Corticosterone in dams, body weight, corticosterone, learning and memory were assessed in male and female offspring at one, two, and three months of postnatal life. Results showed that escape latencies of PS rats of both sexes were longer as compared to those of control groups and that the number of platformsite crossovers and time spent in the platform quadrant were lower in the PS animals as compared to the control groups. Corticosterone levels were higher in PS females and males compared with controls. The body weight was decreased only in PS males of one month of age. These results show that PS by immersion in cold water alters learning and memory processes in the offspring, regardless of sex or age, since the effects are similar in females and males during youth and adulthood. These behavioral effects are related to high serum corticosterone.